Asymptotic symmetries and Weinberg’s soft photon theorem in Mink d+2 - Temple He; Prahar Mitra (Journal of High Energy Physics, 2019)
Abstract We show that Weinberg’s leading soft photon theorem in massless abelian gauge theories implies the existence of an infinite-dimensional large gauge symmetry which acts non-trivially on the null boundaries ± of (d + 2)-dimensional Minkowski spacetime. These symmetries are parameterized by an arbitrary function ε(x) of the d-dimensional celestial sphere living at ± . This extends the previously established equivalence between Weinberg’s leading soft theorem and asymptotic symmetries from four and higher even dimensions to all higher dimensions.